Metodología “Aprendizaje Basado en Competencias” y el Manual de Prácticas de Laboratorio como recurso didáctico para el Aprendizaje de Química Inorgánica con estudiantes del Tercer Semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Ocaña Sañay, Henry Joel (2025)
Competency-Based Learning is a methodology that allows students to autonomously build knowledge by exploiting all their competencies, which must include skills and abilities that facilitate their educational, scientific and technical performance. To do this, the methodology must increase the motivation for learning in the student, as well as the recognition of all their competencies. On the other hand, the Laboratory Practice Manual constitutes an effective source of experimental knowledge since it facilitates the student's development of their competencies, abilities and skills, such as: learning to do, reason, interact with their environment, debate or question ideas. For this reason, the general objective is to propose the "Competency-Based Learning" methodology and the Laboratory Practice Manual as a Didactic Resource for Learning Inorganic Chemistry. The research methodology according to its approach was quantitative, design, non-experimental, objective, basic, level, descriptive, field location and bibliographic. In addition, a survey was applied in Google Forms in which 10 closed questions were asked with 5 response options, concluding that the Laboratory Practices Manual as a teaching resource facilitates the student's experimental work.